Customer Satisfaction and Stock Returns - Fatingan, K (2019)
This study examines the effect of customer satisfaction, represented by the American Customer Satisfaction Index (ACSI), for 128 publicly listed US firms during 2012 to 2018, in three ways. The first method examines the effect of ACSI on market capitalisation. The second part looks at how the ACSI can be utilised to form portfolios with above-market returns. Lastly, the portfolio returns from the second section are entered in Fama-French 3-Factor and 5-Factor models, in order to explain if they deliver excess returns. This research finds that ACSI impacts market capitalisation by 1.6% for every unit change ceteris paribus, which equates to $1.075 billion on average. Furthermore, it is possible to use the ACSI to create portfolios with higher returns. However, when applying these returns in the factor models, only the lower scoring ACSI firms appear to deliver excess returns with statistical significance. This study argues that the market does not fully value intangible factors for firms with a lower ACSI that improve their customer satisfaction rating, whereas firms that score highly every year do not enjoy better financial performance, due to a threshold of diminishment between customer satisfaction and financial metrics.